(3eNJGQ JGQjN HZOGO ddNWjH GdHZOGOis - (3GdNWjH GdHZOGOj , CMeO Hf Ydj Hf KGHJ , CHh HcQ , J (B463 (3g` s ((3eMeO Hf CMeO Hf CHj GdbGSe GdYHGSi GdHZOGOi s)
(3ChdgG (B:s
(3gPG GdcJGH GdPi Ufag GdNWjH GdMGaX GdHZOGOi hSeGg JGQjN HZOGO s
(3BNQgG (B:s
(3Je GdeNJGQ ef eNJUQ HZOGO s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJjGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B3s
Keywords: (3GdJGQjNs